Gender Roles in Pakistani-Urdu Wedding Song - Syeda Bushra Zaidi (JEELS (Journal of English Education and Linguistics Studies), 2016)
This qualitative study of Pakistani-Urdu wedding songs allows a closer look at the gender situation, and towards the understanding of the process of construction and perpetuation of gender-based stereotypes. However, the major concern of this study is to understand the portrayal of each gender along with the question that does such portrayal underlines the traditional gender roles and gender inequality. Taking a discourse analysis perspective, this study analyzes textual data from the lyrics of the seventeen wedding songs. The song selection was based on purposive sampling technique. The data were collected through transcription and recording of the audios of the songs. As a result of thematic analysis thirteen themes emerged, ten portraying the female gender and four portraying the male gender. These themes reveal important findings that support and reinforce the gender-based stereotypes and also reflect gender hierarchy, normative heterosexual relationships, kinship norms and gender subversions.